Balinese Language Lexicon in the Tradition of Installing Penjor at the Galungan Celebration in Sari Bhuana Village, Toili Jaya District - Eka Devi Laksmiasih; Mohamad Karmin Baruadi; Puspita Dian Agustin (Raja Zulkarnain Education Foundation, 2026)
The tradition of installing penjor is a Balinese cultural heritage that is full of values and symbolism. In this tradition, there are various Balinese lexicons used in the process of making penjor during the Galungan celebration, but the understanding of their use and meaning has not been widely studied, especially in Sari Bhuana Village, Toili Jaya District. The lexicon does not only function as linguistic terms, but is also related to the cultural identity and spiritual values of the community. This study aims to examine the Balinese lexicon used in the tradition of installing penjor and analyze the meaning of each element of penjor, such as tieng, wastra, lamak, tebu, biu, and jaje, based on the understanding of the people of Sari Bhuana Village as part of their cultural identity and spiritual values. This study uses a descriptive method to examine the Balinese lexicon in the tradition of installing penjor during the Galungan celebration in Sari Bhuana Village. Data were obtained through observation, interviews, and documentation of the process of making penjor and sources such as the village head, parisada chairman, traditional leaders, and village officials. Data analysis was carried out through reduction, presentation, and drawing conclusions with a focus on identifying terms, functions, and meanings of the lexicon. Data validity was strengthened through triangulation of sources and techniques. The results of the study indicate that the Balinese lexicon in the penjor installation tradition functions not only as linguistic terms but also contains cultural meaning in each of its elements. This lexicon represents the relationship between humans and nature and spiritual values passed down through generations. Based on the results of the study, it can be concluded that the Balinese lexicon in the penjor installation tradition serves as a cultural symbol that conveys a philosophy of life and a form of devotion to the Creator.